Case study on a coniferous plantation site about inter-annual shifts in microbial communities under short-term detritus input manipulations. (November 2021) - Wu, Junjun; Jia, Wei; Zhang, Dandan; Liu, Guihua; Cheng, Xiaoli
Graphical abstract: The variation in microbial community structure among different plant detritus input manipulations over study period. Highlights: Inter-annual variation in microbes was larger than that caused by detritus input. The effect of detritus input change on soil microbes become stronger over time. Changes in soil microbial community were associated with resource availability. Microbial respiration was negatively correlated with fungi to bacteria ratio. Abstract: Soil microorganisms are key regulators of soil carbon (C) and nutrients cycles in terrestrial ecosystems. However, it remains uncertain how the inter-annual variation in soil microbial community corresponds well with resource availability in the changing environment. Here, we investigated soil microbial community structure and abundance, as well as the associated environmental variables from 2015 to 2017 under different plant detritus input manipulation treatments in a coniferous ( Platycladus orientalis (Linn.) Franco) plantation forest ecosystem in subtropical China. Our results showed that the inter-annual variation in soil microbial community was more visible than that caused by detritus input manipulations, owing to the temporal alterations in microclimates and substrate availability. Both aboveground litter removal and root exclusion had more negative effects on the bacterial PLFAs than fungi except half a year after detritus input manipulations. While, soil microbial abundance increased only after three years of litter addition compared to control. Litter removal, especially the no input treatment significantly increased the fungi to bacteria (F:B) and Gram-positive to Gram-negative bacteria (GP:GN) ratios after one and two years of detritus input manipulations. Whereas, the litter addition treatment had minor effects on these parameters. A clear discrimination of microbial community structure among the different detritus input manipulations appeared after two and three years. Both the F:B and GP:GN ratios were positively related to the carbon to nitrogen (C:N) ratio, recalcitrance index of carbon (RIC) and nitrogen (RIN). Overall, our results reveal that the inter-annual variations in soil microbial community are clearly differentiated by the environmental variables and substrate availability that occur in different years and detritus input manipulations. Our results also suggest that due to the vital role of microorganisms in biogeochemical cycling, shifts in the microbial community structure with altered plant detritus input could profoundly affect ecosystem processes in the long run.